Association Between Base Excess and Mortality Among Patients in ICU With Acute Kidney Injury - Cheng, Yi; Zhang, You; Tu, Boxiang; Qin, Yingyi; Cheng, Xin; Qi, Ran; Guo, Wei; Li, Dongdong; Wu, Shengyong; Zhu, Ronghui; Zhao, Yanfang; Tang, Yuanjun; et al. (Frontiers in Medicine, 2021)
Objective This study aimed to explore the association between base excess (BE) and the risk of 30-day mortality among patients with acute kidney injury (AKI) in the intensive care unit (ICU). Methods: This retrospective study included patients with AKI from the Medical Information Mart for Intensive Care (MIMIC)-IV database. We used a multivariate Cox proportional-hazards model to obtain the hazard ratio (HR) for the risk of 30-day mortality among patients with AKI. Furthermore, we utilized a Cox proportional-hazard model with restricted cubic splines (RCS) to explore the potential non-linear associations. Results Among the 14,238 ICU patients with AKI, BE showed a U-shaped relationship with risk of 30-day mortality for patients with AKI, and higher or lower BE values could increase the risk. Compared with normal base excess (-3 to 3 mmol/L), patients in different groups (BE ≤ -9 mmol/L, -9 mmol/L